MTAPIN: multi-touch key input enhances security of PIN authentication while keeping usability. Issue 3 (19th August 2014) - Takada, Tetsuji; Kokubun, Yuki
Abstract : Purpose: The aim of the research is to realize a better form of personal identification number (PIN) authentication for a mobile phone without lowering usability and acceptability. Design/methodology/approach: Our approach is to extend the input operation of PIN authentication by allowing more than one number at a time using a multi-touch enabled screen. We also introduced substitution keys to be able to type any combination of a PIN value and an input pattern by multi-touch typing. Findings: We conducted a user evaluation study using a web-based prototype system. The results of the study indicate that PIN input time, input errors and secret memorability of the proposed scheme were no worse than those of conventional PIN authentication. The theoretical security level of the proposed scheme is almost three and a half times than that of the conventional scheme. Originality/value: The paper introduced a multi-touch allowed secret input operation into a PIN authentication. Though the introduction affected not only an input operation but also a PIN input interface and secret information, it makes possible to realize a better security level without a drastic change of a user interface and taking a longer input time.